Gastrointestinal Bleeding, Jejunum Perforation and Intussusceptions Ileo-Jejunal Segment with Multiple Polyposis Due to Metastasic Melanoma with Out Primary Cutaneus Melanoma? - Lianda Siregar; Mangalindung Ompusunggu (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2004)
Approximately 60% of patients who die due to melanoma have gastrointestinal metastases at autopsy, yet ante mortem diagnosis is uncommon. The small bowel is the most frequent intestinal site of metastasis and prognosis is very poor with a median survival after operation was 6.2 months (range: 1–42 months). Bowel metastases may appear radiologically as polypoid mucosal lesions, submucosal nodules, diffuse infiltration with thickening of the intestinal wall, or serosal implants. Bowel obstruction due into intussusceptions is common clinical presentation of gastrointestinal metastasis; other presentation include gastrointestinal bleeding, perforation and large masses.We reported a case of metastatic melanoma to small bowel, whose had hematemesis melena, abdominal pain, diarrhea and weight loss without primary cutaneus melanoma. Gastroduodenoscopy appeared normal. The ultrasonography of bowel showed a”doughnut” configuration with concentric rings of bowel wall. Left lateral decubitus abdominal radiographies showed free air appearances. Laparatomy reported three location of invagination (intussuception) with multiple polyposis at ileo–jejunal segment (29 pieces of polyp) and jejunum perforation. Resection and end–to end anastomosis of the affected segment had been performed with no serious complication after this. Miscroscopical examination of specimen showed metastatic melanoma malignant in 3 lymph nodes. Eight weeks later patients died with distant metastases to brain. Keywords:  Intussesception and perforation, multiple polyposis, metastase melanoma without primary cutaneus melanoma